2017
DOI: 10.1016/j.scitotenv.2017.07.153
|View full text |Cite|
|
Sign up to set email alerts
|

Settlement patterns of the coral Acropora millepora on sediment-laden surfaces

Abstract: Successful recruitment in corals is important for the sustenance of coral reefs, and is considered a demographic bottleneck in the recovery of reef populations following disturbance events. Yet several factors influence larval settlement behaviour, and here we quantified thresholds associated with light attenuation and accumulated sediments on settlement substrates. Sediments deposited on calcareous red algae (CRA) directly and indirectly impacted coral settlement patterns. Although not avoiding direct contact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 71 publications
1
62
0
Order By: Relevance
“…Of the 61 colonies persisting on our tiles until 8 months, over 80% began as spat that initially settled on a vertical edge or underhang tile surface. Settlement in these semi-sheltered locations would have provided good access to light for photosynthesis 34 and only limited sedimentation 52 , with underhang locations potentially having some protection from predation by corallivorous fish 53 . In contrast, corals that settled on upward facing surfaces would have had abundant light but also higher sedimentation and possibly increased risk of predation, while corals settled on inner bottom surfaces may not have thrived due to insufficient light.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 61 colonies persisting on our tiles until 8 months, over 80% began as spat that initially settled on a vertical edge or underhang tile surface. Settlement in these semi-sheltered locations would have provided good access to light for photosynthesis 34 and only limited sedimentation 52 , with underhang locations potentially having some protection from predation by corallivorous fish 53 . In contrast, corals that settled on upward facing surfaces would have had abundant light but also higher sedimentation and possibly increased risk of predation, while corals settled on inner bottom surfaces may not have thrived due to insufficient light.…”
Section: Discussionmentioning
confidence: 99%
“…A range of toxicants, including metals, pesticides, petroleum products, and other industrial products, have been shown to impact larval settlement (Negri & Heyward 2000, Reichelt-Brushett & Harrison 2000, Negri et al 2005, Lam et al 2015, Hudspith et al 2017, and the physical blocking of cues can impede settlement as well. A very thin layer of sediment, for example, can prevent settlement on substrates with strong cues, and when removed, a legacy impact on the inductive capacity of the substrate may remain (Ricardo et al 2017). Elevated temperature and pCO 2 exposure can also directly reduce settlement rates and increase post-settlement mortality (Randall & Szmant 2009a,b, Albright et al 2010, Heyward & Negri 2010, Albright & Langdon 2011, Doropoulos et al 2012a, but see Putnam et al 2008), but can also negatively impact the biota that induce coral settlement, causing the broad-scale impairment of natural recruitment (Kuffner et al 2008, Doropoulos et al 2012a, Webster et al 2013, Fabricius et al 2015.…”
Section: Settlement Cues and Inhibitorsmentioning
confidence: 99%
“…The shape and topography of artificial substrates can be designed and manufactured to produce an optimal settlement habitat. Larvae are drawn to small crevices and areas free of sediments and grazers (our Section 5.1; Babcock & Davies 1991, Doropoulos et al 2016, Ricardo et al 2017. Several organisations are developing 'seeding units' designed to maximise recruitment success by incorporating natural microrefugia (e.g.…”
Section: Artificial Substrates For Use In Reef Restorationmentioning
confidence: 99%
“…The state of algal turfs is, in‐turn, intimately linked to the sediments they contain (Clausing et al, ; Goatley et al, ; Tebbett et al, ). By mediating key processes such as herbivory (Goatley et al, ; Tebbett, Goatley, & Bellwood, ), coral settlement (Birrell, McCook, & Willis, ; Ricardo, Jones, Nordborg, & Negri, ; Speare, Duran, Miller, & Burkepile, ) and benthic productivity (Tebbett et al, ) sediments can mediate many critical processes of reef systems. This recent recognition of the ecological importance of turf‐bound sediments appears timely, given that more than 50% of reefs are forecast to be at risk of increased terrestrial sediment inputs (Burke, Reytar, Spalding, & Perry, ).…”
Section: Introductionmentioning
confidence: 99%